Contribution of individual excitatory synapses on dendritic spines to electrical signaling - Weng, Ju-Yun; Ceballos, Cesar; Zecevic, Dejan (Frontiers in Neuroscience, 2025)
Dendritic spines, ∼1 μm protrusions from neuronal dendrites that receive most of the excitatory synaptic inputs in the mammalian brain, are widely considered the elementary computational units in the nervous system. The electrical signaling in spines is not fully understood, primarily for methodological reasons. We combined the techniques of whole-cell recording and voltage imaging to study excitatory postsynaptic potentials evoked by two-photon glutamate uncaging (uEPSPs) on individual dendritic spines on basal dendrites in rat cortical slices. We analyzed the initiation, temporal summation, and propagation of uEPSPs from the spine head to the parent dendrites in three principal neocortical pyramidal neuron classes. The data show no significant attenuation of uEPSPs across the spine neck in most tested mushroom spines on basal dendrites. This result implies that synapses on examined spines are not electrically isolated from parent dendrites and that spines do not serve a meaningful electrical role. Using the same imaging techniques, we characterized the temporal summation of uEPSPs induced by repetitive glutamate uncaging, mimicking the burst activity of presynaptic neurons. We found that summing responses to high-frequency repetitive quantal EPSPs is strictly limited in amplitude and waveform. This finding reveals a biophysical mechanism for preventing synaptic saturation.